Integrating Data Science and the Internet of Things Into Science, Technology, Engineering, Arts, and Mathematics Education Through the Use of New and Emerging Technologies - Liston, Maeve; Morrin, Anne M.; Furlong, Trevor; Griffin, Leona (Frontiers in Education, 2022)
Abstract This paper reports on the implementation of a collaborative approach to STEAM (Science, Technology, Engineering, Arts, and Mathematics) education within the context of a college of education and an elementary school in Ireland. The project is novel in that it explores a transdisciplinary approach of supporting STEAM education in a school, using data science and an Internet of Things (IoT) based Environment Monitoring System. This case study contributes to an emerging field of research within STEAM ed that is informed by practice with emphasizes placed on the value of collaboration and transdisciplinary pedagogical approaches. The multi collaborators included lecturers from a college of education with expertise in STEM and Visual Arts education, creative professionals (artists, scientists, architects), teachers, students, and children. Encompassing all the mentioned stakeholders was important and placed (trans) disciplinarity at the core of the learning. Qualitative data was collected using questionnaires, focus groups and interviews to research how the participants interpreted their experiences and what meaning they attributed to their experiences. It was found that a program of STEAM education integrating new and emerging technologies with data science and the IoT can promote and encourage the delivery of a (trans)disciplinary model of STEAM education and the overall reconceptualization of how individual subject areas are taught at elementary level. Innovative data capturing technologies, exploring real-life data within their local educational contexts can positively impact children and teachers’ knowledge and skills in STEAM supporting the development of artistic concepts, engineering habits of mind, imagination, and creativity. The success of the project can be attributed to the collaboration between various stakeholders in the design and implementation of the project. This paper has provided valuable insights into teachers’, scientists and artists’ perspectives, children’s experiences, and the role of innovative technology in STEAM education.